Synthesis, characterization, and electrical, electrochemical and gas sensing properties of a novel cyclic borazine derivative containing three phthalocyaninato zinc(II) macrocycles - ÖZKAYA, ALİ RIZA; ÖZER, METİN (ELSEVIER SCIENCE SA, 2005)
A novel borazine derivative of trinuclear phthalocyanine has been prepared by following the multistep reactions of unsymmetrically substituted phthalocyanines. 4-(4-Amino-3-nitrophenoxy)phthalonitrile (3) which is one of the precursor molecules of the phthalocyanine was obtained from 4-nitrophthalonitrile (1) and 4-amino-3-nitrophenol (2) with K2CO3 in DMF at 50 degrees C. The zinc(II) phthalocyanine (5) containing an unsymmetrical substituted 4-aniino-3-nitrophenoxy group was synthesized by statistical condensation of two different phthalonitriles. 4-(4-Amino-3-nitrophenoxy)phthalonitrile (3) and 4,5-bis(hexylthio)phthalonitrile (4) were cyclotetramerized with zinc acetate in DMF at 170-180 degrees C to yield 2-(4-amino-3-nitrophenoxy)-9,10,16,17,23,24-hexa(hexylthio)phthalocyanine zinc(II) complex (5), which was then separated by column chromatography on silica gel. The unsymmetrically substituted compound was reduced to the diamine form (6) using hydrazine hydrate in the presence of Pd/C catalyst, and the product was purified with chromatographic separation. Compound 6 was then reacted with triisopropoxyborane in refluxing xylene to give 5H,12H,19H-tris[2-(3,4-diaminophenoxy)-9,10,16,17,23,24-hexa(hexylthio)phthalocyaninato zinc(II) diazaborolo] borazine (7). The resulting product was purified by column chromatography on silica gel. All the target unsymmetrical phthalocyanines and borazine derivative were characterized by elemental analysis, IR, UV-vis, and H-1 NMR. Boron and zinc(II) percents in 7 were quantified with ICP-MS. Impedance spectroscopy and dc measurements were performed on spin coated 5-7 films as a function of temperature (293-400 K). The dc results showed an activated conductivity dependence on temperature. The ac results gave a temperature dependent frequency exponent s. The results were compared with the prediction of the Quantum Mechanical Tunelling and Correlated Barrier Hopping models. The ac conductivity of the films was well represented by the form A omega(s). Gas sensing properties of the films for the volatile organic compounds (VOCs) (chloroform, acetone, carbontetrachloride and ammonia) were also investigated in the temperature range from 293 to 400 K. The operating temperature had a considerable effect on sensing characteristics. Maximum sensitivity to VOCs were observed at room temperature for all films. Cyclic voltammetry of compounds 6 and 7 in solution indicated that these compounds have similar voltammetric behaviour. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: zinc phthalocyanine; borazine; electrochemistry; conductivity; gas sensing; LANGMUIR-BLODGETT-FILMS; UNSYMMETRICAL PHTHALOCYANINE; COPPER PHTHALOCYANINE; SUBSTITUTED PHTHALOCYANINES; ELECTROCHROMIC PROPERTIES; THIN-FILMS; COMPLEXES; CONDUCTIVITY; AC; BEHAVIOR